Migration factors among broadband services: Panel data analysis - Sobee Shinohar; Yuji Akematsu; Masatsugu Tsuji (International Telecommunications Society (ITS), 2012)
Providing nationwide deployment of broadband services has become an important national agenda. The U.S. announced a National Broadband Plan and EU a Digital Agenda for Europe, both of which aim at providing access to 100 Mbps broadband services by 2020 to substantial numbers of households. The purpose of this paper is to analyze the migration factors among broadband services, namely CATV (BB), DSL and FTTx, in OECD 30 countries. In so doing, we focus especially on migration from CATV (BB) and DSL to FTTx in OECD 30 countries. Since FTTx is not independent of other two competing broadband services, not only FTTx but also CATV (BB) and DSL are analyzed. The results obtained by empirical panel data analysis, which covers the data from the year 2000 to 2010, revealed that (1) each three broadband services are substitutes, (2) faster connection speed promotes each broadband services adoption, (3) initial conditions of Cable TV in 2000 promote CATV (BB) diffusion, (4) unbundling of dry copper promotes DSL diffusion, (5) unbundling of fiber local loop restricts FTTx diffusion, and (6) investment decision on FTTx by carriers affects FTTx diffusion. This analysis will provide an important basis for national broadband policy in each country.
Keywords: 330